The Culture of Consumption as a Consequence of the Economic Process in the Context of Changes in the European Union - Pieszak, Eryk (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
In the article, through a comparative analysis of the discourse related to the description of economic free market processes and discourses related to cultural processes, we are looking for a research perspective that allows to examine the mutual influence of these cultural processes. If we analyze the descriptions of socio-economic changes in countries such as Poland or the Baltic countries, it turns out that their path to increase economic competitiveness is similar. It is associated with market changes but also a cultural change in a broader context. Thus, one can hypothesize: the individual is free in the world of thought, however, in the world of phenomena, freedom does not exist. This hypothesis developed for societies that introduced a free market would be: the individual in the consumer society is free in the world of his thoughts but in the world of market phenomena he is subject to independent processes.

W artykule poprzez analizę porównawczą dyskursu związanego z opisem ekonomicznych procesów wolnorynkowych i dyskursów związanych z procesami kulturowymi szukamy perspektywy badawczej, pozwalającej badać wzajemny wpływ tych procesów kulturowych. Jeżeli przeanalizujemy opisy przemian społeczno-gospodarczych, krajów takich, jak Polska czy kraje Nadbałtyckie, okaże się, że droga ich do zwiększenia konkurencyjności ekonomicznej jest podobna. Wiąże się ona ze zmianami rynkowymi, ale także przemianą kulturową w szerszym kontekście. Można więc postawić hipotezę: jednostka jest wolna w świecie myśli jednak w świecie zjawisk wolność nie istnieje. Hipoteza ta rozwinięta na społeczeństwa, które wprowadziły wolny rynek brzmiała by: jednostka w społeczeństwie konsumpcyjnym jest wolna w świecie swoich myśli, lecz w świecie zjawisk rynkowych podlega niezależnym od niej procesom.
Kultura konsumpcji jako konsekwencja procesu ekonomicznego w kontekście przemian na terenie Unii Europejskiej
Keywords: free market; consumption; culture; consumption culture; consumer society; wolny rynek; konsumpcja; kultura; kultura konsumpcji; społeczeństwo konsumpcyjne